The Time-Life Encyclopedia of Mysterious Places : The Life and Legends of Ancient Sites Around the World - Illustrated by Ingpen, Robert, 1936- (Alexandria Time Life Books, 1990)
For anyone who has ever been captivated by the mysteries abounding in the lore and legends of the past, this is the perfect traveler's companion to carry along on those voyages back in time.
Include Color Illustration and Index
Keywords: Mythology -- Antiquities -- Civilization, Ancient